Enhancing Arabic Reading Comprehension through the Lost in Translation Strategy: A Mixed-Methods Study: Meningkatkan Kemampuan Membaca Bahasa Arab melalui Strategi Lost in Translation: Sebuah Studi dengan Pendekatan Campuran - Hudzaifah; Mukmin; Rendi Sabana (UIN Raden Mas Said Surakarta, 2026)
The teaching of reading Arabic at Raudhatul Ulum Sakatiga Islamic Senior High School shows that students still rely on literal translations, so they don't fully understand the text's meaning. This condition creates a gap between technical reading skills and advanced reading comprehension. This study aims to optimize Reading Comprehension learning through the application of the Lost in Translation strategy, which is a contextual meaning approach that emphasizes global meaning analysis, cultural elements, and inter-sentence relationships. The study used a mixed methods approach with a sequential explanatory design, involving 20 tenth-grade students through pre-tests, post-tests, observations, interviews, and questionnaires. Quantitative data were analyzed using normality, homogeneity, and paired sample t-tests, while qualitative data were analyzed descriptively. The results showed an improvement in students' reading skills, as seen from the pre-test average of 64.75, which increased to 69.55 in the post-test. The paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference after the strategy was applied. Qualitatively, students became more active, able to connect ideas between sentences, and more accurate in capturing the global meaning of the text. This study confirms that the Lost in Translation strategy is effective in improving reading comprehension through an interpretive approach that does not rely on word-by-word translation. The recommendation for further research is the development of meaning-based digital media to strengthen the implementation of this strategy in various learning contexts.